Parent as both perpetrator and victim: blame and punishment in a case of child neglect - Hanson, Bridget L. (Applied psychology in criminal justice, 2015)
Attributions of responsibility typically increase as outcome severity increases. In defensiveattributions, similar others are assigned less responsibility in more severe instances. Thecurrent study utilized a child neglect paradigm to explore defensive attributions when theactor may be perceived as both perpetrator and victim. Participants read a newspaper articlein which a parent left a child unattended in a hot car, with details based on participants'random assignment to one of four experimental conditions (outcome severity: mild vssevere; actor gender: male vs female). Results failed to support the defensive attributionhypothesis for attributions of controllability, responsibility, and blame. However, groupdifferences based on actor-observer similarity of gender and parenting status were foundfor empathy, and empathy predicted social punishment.